Math

Question 1

 

 

If a - 5 = 12y and 2a + 3 = -2y, then y =

 

(A) 2

(B) -1

(C) 1/2

(D) -1/2

(E) -1/6

 

 

To find y, we have to eliminate the variable a. We do this by combining the two equations. If we multiply the first equation by two, we can subtract the resulting equation from

the second one:

 

 

 

 

 

Subtracting the bottom equation from the top, we get:

 

   13 = -26y

 

When we divide both sides by -26:

 

   y = 13/-26 = -1/2  (Answer D)

 

 

You can check this answer by plugging -1/2 in for y in the original equations. In both cases, a should equal -1 (but be careful: that isn't the answer to the original question.)

 

 

 

2a + 3 = -2y

2a - 10 = 24y

2a + 3 = -2y

a - 5 = 12y

Question 2